CLIL (CONTENT AND LANGUAGE INTEGRATED LEARNING) THROUGH INTERDISCIPLINARY INTEGRATION IN TEACHING ENGLISH (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the theoretical and methodological foundations, didactic advantages, and practical opportunities of teaching English through interdisciplinary integration based on the CLIL (Content and Language Integrated Learning) approach. The study examines the content component of CLIL, the principles of parallel development of language skills and subject knowledge, as well as the approach’s impact on learners’ competencies.